An Analysis of the Effect of Team Situation Awareness on Patient Safety Incidents using Teamwork as the Intervening Variable - Paramita, Ristiya Galih; Wijaya , Terivenna; Chalidyanto, Djazuly; Asih, Akas Yekti Pulih (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
The definition of Patient Safety Incidents (PSIs) refers to specific occurrences that unintentionally happen and result in, or potentially lead to, injuries in patients if not prevented. PSIs require special attention, especially in healthcare settings. According to the report collected by the Hospital Patient Safety Committee of the Surabaya Orthopedic and Traumatology Hospital from 2018 to 2021, there were 177 patient safety incidents recorded. This study aims to analyze the effect of Team Situation Awareness (TSA) on Patient Safety Incidents through Teamwork at Surabaya Orthopedic and Traumatology Hospital. The variables identified for analysis are Team Situation Awareness (TSA) and Teamwork. Because this study was conducted over a specific time period, it follows a cross-sectional design and is an analytical observational study. Path analysis was employed to analyze the data. The measurement revealed that TSA resulted in 64.3% of work units being categorized at level 2 (comprehension), and for Teamwork, 64.3% of the works units were categorized as “Good”. The results of the Path Analysis using SmartPLS 4.0 showed the effect of TSA was significant with a p-value of <0.05, and TSA’s effect on Teamwork was also significant with a p-value of <0.05. Based on the path analysis (SEM-PLS), it was found that TSA indirectly affected PSIs through Teamwork, with a significant indirect effect having a p-value <0.05. Team Situation Awareness indirectly influenced PSIs through Teamwork.  One approach to reducing the frequency of PSIs is to improve Team Situation Awareness (TSA) within each work unit at Surabaya Orthopedic and Traumatologic Hospital.   Keywords: Patient Safety Incidents, PSIs, team situation awareness, TSA, teamwork